Growth Performance of Albino Rats Fed Graded Levels of Baobab (Adansonia digitata) Leaf Meal - Abdul-Rahaman Saibu Salifu; Ayimbire Abonuusum; Joseph Kinansua Laary (Archives of Current Research International, 2016)
Aims: The study was conducted to determine the possible use of baobab leaf meal (BLM) as a feed ingredient in livestock feeding and its effects on growth performance of the animals. Study Design: Completely Randomized Design (CRD) was used for the study. Place and Duration of Study: Department of Ecological Agriculture, Bolgatanga Polytechnic, Bolgatanga. The experiment lasted for four weeks. Methodology: Sixteen individually-housed albino weanling rats of about six weeks old were fed with four levels of BLM inclusion in the diet. The four levels of BLM in the diets were the control (0%), 10%, 15% and 20% for T0, T1, T2 and T3 respectively. Each treatment was replicated four times, with a rat representing a replicate. Feed and water were given ad-libitum and growth performance monitored during the four-week period. The data were analyzed using the General Analysis of Variance. Least significant difference was also used to separate treatment means at 5%. Results: The results showed significant differences (P=.05) between levels of BLM in diet on rats weight gain, feed intake and feed conversion efficiency. The rats fed on the control (T0) diet significantly (P=.05) grew better, compared to those fed with BLM-based diets (T1, T2 and T3). The values for mean weight gain were 59.7, 42.3, 33.3 and 33.3 g for T0, T1, T2 and T3 respectively. In respect to feed intake, the mean total feed intake values were 399.0, 314.0, 327.0, and 313.0 g with corresponding mean daily feed intake of 14.24, 11.21, 11.69 and 11.19 g for T0, T1, T2 and T3 respectively. The mean feed conversion efficiency was better compared to test diets (T1-T3). For the carcass parameters, the mean weights of viscera, respiratory tract, full stomach, heart, kidney, spleen, liver and full gastrointestinal tract were not influenced (P = .05) by the dietary treatments. Conclusion: The inclusion of baobab leaf meal in rat diet could negatively affect their growth performance, especially with regard to their weight gain. In places where other plant-based feed sources are scarce, very low inclusion rates of not more than 10% of BLM in diets may be considered, provided animal weight gain is not the primary objective of the farmer.